PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL SELF EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR UMKM DI PULAU KODINGARENG KECAMATAN SANGKARRANG - Asiyah, Nur; Halim, Hasyim; Asdar, Muh. (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of Financial Knowledge and Financial Self-Efficacy on the Financial Management Behavior of MSME actors on Kodingareng Island, Sangkarrang District. Data collection used primary data obtained from questionnaires using saturated sample techniques. The population is all MSMEs on Kodingareng Island, Sangkarrang District, as many as 36 MSMEs, while the sample that can be collected is 36 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions in the form of normality assumptions, multicollinearity assumptions, and heteroscedasticity assumptions. The data analysis method uses multiple regression techniques. The results of the study show that Financial Knowledge has a positive and significant effect on financial management behavior, while Financial Self-Efficacy has a positive but insignificant effect. Simultaneously, these two variables have a significant influence on Financial Management Behavior. These findings affirm the importance of increasing financial literacy and strengthening self-confidence in supporting the success of financial management and the sustainability of MSME businesses in the archipelago.